The clinical application of metformin in children and adolescents: A short update - Soliman , Ashraf; De Sanctis, Vincenzo; Alaaraj , Nada; Hamed , Noor (Acta Biomedica Atenei Parmensis, 2020)
Summary. Metformin is a widely used drug that results in clear benefits in relation to glucose metabolism and diabetes-related complications. The global increase in the prevalence of obesity among children and adolescents is accompanied by the appearance and increasing prevalence of insulin resistance, prediabetes, and type 2 diabetes mellitus (T2DM). In addition, children, and adolescents with premature pubarche and polycystic ovary have considerable degree of insulin resistance. The insulin sensitizing actions of metformin encouraged many investigators and physician to use it as the key drug in these conditions for both prevention and treatment. However, long term-controlled studies are still required to assess the degree and duration of effectiveness and safety of using metformin. This review tries to update physicians about the main and the new therapeutic perspectives of this drug.